1986
DOI: 10.1002/j.2050-0416.1986.tb04373.x
|View full text |Cite
|
Sign up to set email alerts
|

The Chemistry of Nitrosamine Formation: Relevance to Malting and Brewing

Abstract: This paper reviews the chemistry of nitrosamine formation with special reference to malting and brew ing. Whilstthe main emphasisison the formation of nitrosodimethylamine(NDM A), the chemistry is also related to the formation of other nitrosamihes and certain other nitrocompounds. It seems likely that in malting and brewing the only important source of the nitroso group is the mixture of oxides of nitrogen (NO,) in the hot air in contact with malt during kilning. Under normal commercial conditions there appea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
21
0
4

Year Published

1987
1987
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(25 citation statements)
references
References 48 publications
0
21
0
4
Order By: Relevance
“…Podle atomu, na který je tato skupina vázána, lze dále rozlišovat C-, N-, S-a O-nitroso sloučeniny. Tyto látky mohou vznikat přímým působením nitrosačních činidel na příslušné prekurzory nebo prostřednictvím transnitrosač-ních reakcí, kdy je nitroso skupina přesunuta z jedné molekuly na jinou (Wainright, 1986a). Nejvýznamnějšími nitrososloučeninami v potravinářství jsou N-nitrososloučeniny, konkrétně N-nitrosaminy.…”
unclassified
See 3 more Smart Citations
“…Podle atomu, na který je tato skupina vázána, lze dále rozlišovat C-, N-, S-a O-nitroso sloučeniny. Tyto látky mohou vznikat přímým působením nitrosačních činidel na příslušné prekurzory nebo prostřednictvím transnitrosač-ních reakcí, kdy je nitroso skupina přesunuta z jedné molekuly na jinou (Wainright, 1986a). Nejvýznamnějšími nitrososloučeninami v potravinářství jsou N-nitrososloučeniny, konkrétně N-nitrosaminy.…”
unclassified
“…They can be further divided into C-, N-, Sand O-nitroso compounds. These substances are formed by direct reaction of nitrosating agents with appropriate precursors or by transnitrosation reactions, in which the nitroso groups are transferred from one molecule to another (Wainright, 1986a). N-nitroso compounds, especially N-nitrosamines, are the most important nitroso compounds in food industry.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…In the stomach, nitrite is protonated producing nitrous acid (pKa = 3.3), an oxidizing and nitrosating agent, to react with food components. It is well known that nitrous acid can transform amines into carcinogenic compounds nitrosoamines [10], and it has been reported that phenolic compounds can reduce nitrous acid to a functional compound nitric oxide ( • NO) [11,12]. The functions of • NO produced in the gastric lumen include the increase in gastric mucosal blood flow, the increase in gastric mucus thickness, and the relaxation of gastric smooth muscle [13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%